Optimalisasi Limbah Bonggol Jagung untuk Pangan: Kontribusi terhadap Zero Waste dan Keberlanjutan - Barkah, Faridha Noer; Pratama, Anisa Oktina Sari; Lestari, lara Dwi (WISE Pendidikan Indonesia, 2025)
Corn production in Indonesia will reach 23.6 million tons in 2023 (BPS, 2024), but more than 40% of harvest is organic waste such as cobs, skins, and stalks that are generally not used productively. This was often burned or simply thrown away, contributing to environmental pollution and waste of resources. study aims to explore the potential for optimizing corn waste as an alternative food raw material within framework of a zero waste approach and agricultural sustainability. Through literature analysis and stu of innovative practices, it was found that corn waste can be processed into high-fiber flour, fermenta materials, and other functional food components. This innovation supports waste reduction, food so diversification, and increased added value in the agricultural sector. However, the challenges faced inc limited processing technology, lack of supporting regulations, and low farmer awareness of the econo value of waste. Therefore, integration between research, appropriate technology, and inclusive polici needed so that the use of corn waste can contribute significantly to a sustainable and competitive agricult system. One of them is through innovation in processing corn cobs into healthy snacks, which includes drying and grinding stages, the mixing of ingredients, forming and frying, and the last is packaging.